Rekonstruksi Perobekan Bendera Hotel Yamato Menggunakan Augmented Reality Dengan Penanda Gis - Andre Satria Ardiwardhana; Anang Kukuh Adisusilo; Beny YV Nasution (Informatics Engineering Department-UWKS, 2021)
Historical events in Indonesia, especially tearing Flag Hotel Yamato now have less value of interest to the public at this time. As a result, nearly half the population in Indonesia forget it. Various attempts have been made in order to remain in the memories of these events by the Indonesian community. documentation ever made only using the medium of books or movies, but at this point the book and documentary are rarely demand by the public. This happens because of the very rapid technological advances made more attractive smartphone. So it is necessary to document using the latest technologies. The concept of the new technologies that will be used for documentation of historic events that Augmented Reality. Augmented Reality Event aims to Reconstruct tearing Flag Hotel Yamato which will provide a new attraction, because people now are using smartphones. So so is appropriate if Reconstructing events Yamato's tearing flag can be set using Augmented Reality.